ENGINEERING METHOD OF FAULT-TOLERANT SYSTEMS SIMULATION - Larkin, Evgenii V.; Privalov, Aleksandr N. (Journal of Applied Engineering Science, 2019)
Autonomous fault-tolerant systems, operated at hard environment, are considered in this paper. It is shown that common method of units failure compensation, based on an introduction to the system a structural redundancy, leads to the increase of weight/size factor and energy consumption, but sometime does not prolongs its lifetime. The new approach to fault/recovery process modeling, based on use of fundamental apparatus of parallel semi-Markov process, in which ordinary processes simulate the life-cycle of individual units, and the complex process, assembled from ordinary processes, simulates reliability system as a whole, is proposed. Dependences for calculation of time intervals and probabilities of wandering through ordinary semi-Markov processes, with use of the recursive method are obtained. It is shown, that when there is rather complex model of unit life-cycle, semi-Markov process would be replaced with more coarse Markov process. Notions of complex semi-Markov process, such as functional states and semi-Markov matrices Cartesian product are introduced. Theoretical results obtained are confirmed by the practical calculation of the reliability indicators of the system with passive redundancy.